Pelvic and buttock hypoplasia reconstructed with anatomical breast implants. (12th January 2018) - Page, Felicity; Harb, Ayad; Titley, Garth
Abstract : Radiation therapy is used in the management of a number of childhood cancers and can have significant effects on skeletal growth. We present the case of a 35-year-old woman who developed a hypoplastic pelvis and buttocks following radiotherapy for rhabdomyosarcoma of the vagina at the age of 2. At the age of 25, the patient underwent bilateral buttock augmentation with a two-stage reconstruction using tissue expansion followed by definitive augmentation with anatomical breast implant insertion. The patient continues to have a satisfactory outcome 10 years following reconstruction, having undergone a single uplift procedure and exchange of implants through the original incision 9 years postoperatively. This case represents a unique reconstructive challenge to plastic surgeons and was successfully managed with a novel approach.